The Family–School Linkage in Addressing Bullying in Hong Kong: A Sociocultural Perspective. Issue 6 (2nd November 2018) - Liu, Dian; Wong, Sing-wing Dennis; Roland, Erling
Abstract: The phenomenon that around ten percent of schoolchildren are bullied regularly in Hong Kong has attracted much scholarly attention in anti-bullying research. Current literature suggests taking into consideration the contextual features and socioeconomic factors in anti-bullying research, instead of applying identical intervention/prevention measures across cultures. Therefore, this article examines the role of school-family linkage as a mirror of the wide social-culture context, and analyzes the functions of such linkage in anti-bullying practice in Hong Kong. This study was conducted following a film approach in 2015. That is, a group of middle school teachers in Hong Kong were invited to watch small films showing typical bullying and anti-bullying episodes, followed by semi-structured interviews. The article demonstrates a list of good practices representing the functioning of a positive family-school linkage in bullying addressing. However, parental involvement does not always facilitate and can hinder bullying addressing on campuses. This study implies that efficient bullying addressing aligns with parental involvement in the intervention process, suggesting more parental involvement and more collaboration between family and school in anti-bullying. It also raises an urgent question in regards to balancing the various opinions between parents and teachers in child-raising and bullying addressing. This article suggests further and more investigations examining anti-bullying from a socioeconomic perspective.